Insight into the Structure Elucidation of Flavonoids ThroughUV-Visible Spectral Analysis of Quercetin Derivatives Using Shift Reagents - Bajracharya, Gan Bahadur; Paudel, Mohan; KC, Rajendra (Journal of Nepal Chemical Society, 2017)
available with fulltext